Analisis Pemilihan Subbagian Sistem Pengadaan Material Bangunan Teknopark dengan metode Analisis Hirarki Proses (Studi Kasus PTN X) - Yudhanegara, Darmawan; Putri, Pandena Kicky Basuki; Sutartiah, Farliana (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This research aims to find a subsection of the procurement system as an optimal choice in management. The system management studied is the construction of a contextual technopark at PTN X Analysis using by Analytical Hierarchy Process ae past and accurately therefore the results of modeling and processing show that the decision value reaches 0.03165 for industry, 0.1772 for infrastructure, 0.0733 for sustainability, 0.0733 for partnerships, 0.36238 for location, 0.0733 for local government, 0.1772 for capital, and 0.03165 for labor, so the largest is the location factor in the procurement management system optimal.   Keywords: Management, optimal, procurement, technopark